Effects of Early-Stage Treeline Shifts on Soil Microbial Biomass and Catabolic Diversity in Reserved and Grazed Subalpine Meadows - Kristina Ivashchenko; Anastasiya Romanova; Sofia Sushko; Anna Zhuravleva; Anna Kvitkina; Anna Khodzhaeva; Nadezhda Ananyeva (Plants)
Treelines are advancing upward on mountain slopes due to climate warming and reduced grazing intensity. However, the effects of initial vegetation changes on soil C, N, and P retention, microbial biomass, and catabolic diversity in the subalpine meadows during the early stages of treeline shifts remain poorly understood. This research aimed to better understand the direction and drivers of microbial processes related to C, N, and P cycles in the soil of subalpine natural and grazed meadows, with treatments involving meadow grasses alone (GR, control) and as a mixture with forest litter, specifically birch leaves (BLs), in a one-year microcosm experiment. The addition of BLs with GR resulted in a 12–67% decrease in the retention of C, N, and P in soil microbial biomass, but an 8–9% increase in catabolic diversity compared to the control. The most pronounced effect was observed in the N content of the soil microbial biomass (MBN) for both land uses. The increased proportion of recalcitrant plant residue fractions (acid-insoluble and non-polar extractables) contributed to the decrease in soil MBN content. This shift also reduced the microbial metabolic response to carbohydrates in total substrate-induced respiration, leading to a more balanced and catabolically diverse microbial community. These results improve our understanding of the early response of C, N, and P cycling in mountain soils to treeline shifts mediated by climate warming.